Assessment of variational fundamental solution based elements in plate bending dynamics. (January 2021) - Elsheikh, Elsayed M.; Naga, Taha H.A.; Rashed, Youssef F.
Abstract: In this paper, an assessment of the accuracy performance of a new fundamental solution based element is carried out. Dynamic analysis of shear-deformable plate bending problems is considered. The element stiffness matrix is obtained by modified hybrid displacement variational statement. The mass matrix is computed using the relevant element shape functions. Free and forced vibrations are considered. It has demonstrated that the element is suitable for modelling both thin and thick plates. The obtained results are very promising as the accuracy level is excellent even with coarse discretization. The present element could be also considered as a locking-free element.